EFFECT OF Plant Growth Promothing Rhizobacteria DOSAGE OF Eleusine indica ROOTS AND VARIOUS SOIL WATER CONTENT ON PRODUKTIVITY OF Clitoria ternatea - B. D., Kurniawan; Roni, N. G. K.; Wirawan, I W. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the interaction between the dose of plant growth promoting rhizobacteria (PGPR) Eleusine indica roots with water level and the affect of each factor on the growth and yield of Clitoria ternatea plants. This research was conducted in the Greenhouse of Sading Village. This research lasted for 10 weeks, using a complete randomized design with 2 factors, the first factor is the dose of PGPR consisting of D0 = 0 ml / pot, D1 = 10 ml / pot, D2 = 20 ml / pot and the second factor is the water content consisting of K1 = 25%, K2 = 50%, K3 = 75% and K4 = 100% field capacity (KL). There were 12 treatment combinations and each treatment was repeated three times, so there were 36 experimental units. The variables observed were growth variables, yield variables, and growth characteristics variables. The results showed that there was no interaction between the dose of Eleusine indica root PGPR and water content on all variables. The Eleusine indica root PGPR factor tends to show the highest results on the provision of PGPR doses of 10 ml/pot on Clitoria ternatea productivity. Water content tends to show the highest results in the provision of 100% field capacity of Clitoria ternatea plant productivity. It is concluded that there is no interaction between the dose of Eleusine indica root PGPR and various water levels on all variables, the treatment of PGPR dose of Eleusine indica root 10 ml /pot and 100% field capacity tends to give the best response in affecting the productivity of Clitoria ternatea plants.